Curtain wall facades in public buildings in coastal cities: (a case study of Derna city) (Comprehensive Journal of Science, 2026)
This research examines curtain wall facades in public and private buildings in the city of Derna, with the aim of analyzing their types and their compatibility with architectural standards and requirements. It focuses on the extent to which these facades comply with local values ​​and requirements from an architect's perspective, as well as their harmony with the natural environment and the surrounding climate. A survey of architects and specialists was conducted, using a questionnaire, to measure their level of satisfaction with this type of facade. The focus was on achieving sensory qualities that strengthen the relationship between the facade and the building, highlighting architectural elements that embody the identity of curtain wall facades, and contributing to the promotion of ethical values ​​in engaging with the local environment. The research also delved into achieving the physical qualities that contribute to the facades' practical and interactive performance, leading to the philosophical qualities that reflect the city's rich architectural heritage and express its cultural identity. Based on the findings, scholarly discussions were conducted, supported by illustrative drawings and diagrams, to demonstrate the extent to which they align with the participants' opinions and assessments, while offering recommendations to help improve the future use of this type of façade.